Clinical Trial of Herbal Treatment Gene-Eden-VIR/Novirin in Oral Herpes - Hanan Polansky PhD; Adrian Javaherian MSc; Edan Itzkovitz MD (SAGE Publishing, 2018)
Background. Our previous articles showed that suppressive or preventive treatment with the herbal Gene-Eden-VIR/Novirin reduced the number and duration of genital herpes outbreaks with no adverse effects. These studies also revealed that the herbal Gene-Eden-VIR/Novirin is mostly superior to acyclovir, valacyclovir, and famciclovir drugs in genital herpes. This study tested the effect of Gene-Eden-VIR/Novirin in oral herpes (also called cold sores and fever blisters). Methods. The framework of the study was a retrospective chart review. The study included 68 participants. The participants took 1 to 4 capsules per day over a period of 2 to 36 months. The study included 2 Food and Drug Administration-recommended controls: baseline and a no-treatment. Results. Gene-Eden-VIR/Novirin was effective in 89.3% of participants. The treatment reduced the mean number of outbreaks per year from 6.0 and 3.6 in the control groups to 2.0 in the treatment group ( P < .0001 and P = .07, respectively). Gene-Eden-VIR/Novirin reduced the mean duration of outbreaks from 9.8 and 5.8 days in the control groups to 3.2 days in the treatment group ( P < .0001 and P = .02, respectively). There were no reports of adverse experiences. Gene-Eden-VIR/Novirin was compared to acyclovir and valacyclovir in 6 tests. In all tests, Gene-Eden-VIR/Novirin showed higher efficacy. Gene-Eden-VIR/Novirin also showed superior safety. Conclusions. This clinical study showed that suppressive or preventive treatment with the herbal Gene-Eden-VIR/Novirin reduced the number and duration of outbreaks in oral herpes without any adverse effects. The study also showed that the herbal Gene-Eden-VIR/Novirin had better clinical effects than acyclovir and valacyclovir, the leading drugs in the category. Based on these results, we recommend using the herbal Gene-Eden-VIR/Novirin as preventive treatment for oral herpes and, specifically, as an alternative to the acyclovir and valacyclovir drugs.